The Influence of lifestyle, Class of Social, Income and Costumer Personality Character Subjective on Decision to Purchase Traditional Food from UMKM in Millenial Generation : Pengaruh Gaya Hidup, Kelas Sosial, Pendapatan dan Karakter Kepribadian Konsumen Terhadap Keputusan Pembelian Produk Makanan Tradisional UMKM pada Generasi Millenial - Safira; Irianto, Heru; Handayani, Sugiharti Mulya (Procedia of Social Sciences and Humanities, 2022)
The globalization crisis experienced by society today due to the corona virus pandemic has an impact on the industrial and business sectors. This is influenced by people who are more introspective of their daily needs expenditures because they are worried about economic issues related to the recession. As a result, people's buying interest has become sluggish which has resulted in many industries, especially UMKM, which are one of the sources of Indonesia's GDP. This study focuses on knowing the purchasing decisions of traditional food products from UMKM. The method used in this research is descriptive by using survey techniques in taking the sample. The research location is in Surakarta City by determining the sample criteria purposively. The method of determining the sample using 150 samples. The sample criteria using the millennial generation are residents of the city of Surakarta aged 21-41 years. Meanwhile, the data collection method used an online questionnaire distributed through social media. The data analysis method uses SEM which is analyzed with AMOS 22 software. The results of the SEM analysis show that the goodness of fit is relatively good and can be considered to meet the model fit, namely with CMIN/Df = 1.301; TLI= 0.981; CFI= 0.989; NFI= 0.935; IFI= 0.989; RFI= 0.923 and RMSEA= 0.045; GFI = 0.938 while for AGFI it has not fulfilled. The estimation results of the model show that purchasing decisions are not influenced by lifestyle (β = 0.063; cr = 2.556), purchasing decisions are influenced by social class (β = 0.265; cr = 6.03) and consumer personality characteristics (β = 0.316; cr = 6.72) and income also affect purchasing decisions (β= 0.33; cr= 7.043). The relationship between the variables of the structural equation model of this study generally supports the results of previous studies, except for the relationship between purchasing decisions and lifestyle.